Patriotism in the digital era - Nor Azhar, Ahmad (New Straits Times Press (M) Bhd., 2023)
LETTERS: In 1997, the corridors of Institut Teknologi Mara, now known as Universiti Teknologi Mara, echoed with the sounds of students engrossed in their studies.